Capturing Tacit Knowledge in oil and gas project Using Storytelling - Mohd Syafiq b. Saifullah, Mohd Syafiq (Universiti Teknologi Petronas, 2012)
Knowledge plays a vital role in managing project. Generally, knowledge is being categorized into two: explicit and tacit. Tacit knowledge is the .Icnow - how" knowledge that lies in expert's head, while explicit knowledge is wriuen and codified knowledge. Both are long term assets to ev€ry project and putting effort to nurture them is very critical. Though so, most projects are having ditrculty in sharing tacit knowledge because of its nature that preve,lrted the knowledge from being articulated and formalized. Therefore, integrating knowledge mnnagEneNf into project enables tacit knowledge to be captured, codified, and then shared across the project. One ofthe best ways in sharing tacit knowledge is using storytelling. As part of knowledge management, storytelling offers sharing of a more strucmred and absorbable form of tacit knowledge. This paper shares a viewpoint of knowledge sharing in oil and gas project since the indusry embraces lots oftechnical skills ad experience based learning. Besides, this paper pres€Nrts the research methodology which begins with planning until the development process.